2005
DOI: 10.1590/s1678-91992005000100006
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution studies of bee venom and spider toxin using radiotracers

Abstract: The use of radiotracers allows the understanding of the bioavailability process, biodistribution, and kinetics of any molecule labelled with an isotope, which does not alter the molecule's biological properties. In this work, technetium-99m and iodine-125 were chosen as radiotracers for biodistribution studies in mice using bee (Apis mellifera) venom and a toxin (PnTX2-6) from the Brazilian "armed" spider (Phoneutria nigriventer) venom. Incorporated radioactivity was measured in the blood, brain, heart, lung, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 9 publications
1
7
1
1
Order By: Relevance
“…Our results indicated a strong presence of labeled PnTx2-6 in the penis (Figure 5), suggesting the existence of binding sites for this toxin in the rat corpus cavernosum. Our study did not detect differences in the brain, as observed by Yonamine [27]. In addition, when compared with the penis (Figure 5), the amount of labeled toxin in this organ, was increased by a factor of 4.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…Our results indicated a strong presence of labeled PnTx2-6 in the penis (Figure 5), suggesting the existence of binding sites for this toxin in the rat corpus cavernosum. Our study did not detect differences in the brain, as observed by Yonamine [27]. In addition, when compared with the penis (Figure 5), the amount of labeled toxin in this organ, was increased by a factor of 4.…”
Section: Discussioncontrasting
confidence: 42%
“…Interestingly, one of these genes, Sparc , influences several biological activities, including vascular function as it modulates smooth muscle relaxation machinery [26]. Moreover, radiolabeled PnTx2‐6 ( 125 I‐PnTx2‐6) was injected (s.c.) into mice, which was found to be localized in the testis [27].…”
Section: Introductionmentioning
confidence: 99%
“…In mice injected subcutaneously with venom (0.25 mg/kg), the peak serum concentration was observed 15 min post-venom and remained detectable for up to 8 h post-venom (Chávez-Olórtegui et al 2001). With regard to the tissue distribution of P. nigriventer toxins, Yonamine et al (2005) used 125 I-labeled PnTx2-6 to examine the tissue distribution of this toxin in mice. In the circulation (blood), the toxin showed bicompartmental kinetics, with a rapid a phase and much slower b phase.…”
Section: Venom Kineticsmentioning
confidence: 99%
“…Important biochemical, physiological, and pathological tools for the development of new drugs have arisen due to research on animal venoms [1, 2]. …”
Section: Introductionmentioning
confidence: 99%